2021
DOI: 10.3389/fgene.2021.768041
|View full text |Cite|
|
Sign up to set email alerts
|

RNA m6A Methylation Regulators Multi-Omics Analysis in Prostate Cancer

Abstract: RNA N6-methyladenosine (m6A) methylation is known to be the most popular RNA modification in animals. Many research reports have elaborated on the effects of m6A regulators in medical practice, such as diagnosis, prognosis, and treatment. M6A modification has evident impacts on many aspects of RNA metabolism, just like RNA splicing, processing, translation, and stability. M6A also has a magnificent role in numerous types of cancers. We analyzed the prostate cancer datasets, from The Cancer Genome Atlas (TCGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…Similarly, we also found that multiple m6A regulators were dysregulated in PCa. However, m6A regulators related to the progression-free interval, including CBLL1, EIF3A, ELAVL1, FTO, G2BP2, HNRNPA2B1, METTL3, and ZC3H13, were partially different from those including RBM15B, METTL3, HNRNPA2B1, RBMX, YTHDF1 and HNRNPC in a previous bioinformatic study (55). This discrepancy was due to the different samples included in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Similarly, we also found that multiple m6A regulators were dysregulated in PCa. However, m6A regulators related to the progression-free interval, including CBLL1, EIF3A, ELAVL1, FTO, G2BP2, HNRNPA2B1, METTL3, and ZC3H13, were partially different from those including RBM15B, METTL3, HNRNPA2B1, RBMX, YTHDF1 and HNRNPC in a previous bioinformatic study (55). This discrepancy was due to the different samples included in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Corresponding bioinformatics analysis studies have also found DNA mutations and CNVs of m6A regulators ( 54 ). A previous bioinformatic study of m6A regulators in PCa showed that the expression of most m6A regulators was dysregulated and that some regulators were related to survival ( 55 ). Similarly, we also found that multiple m6A regulators were dysregulated in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Recent computational studies have found a complex scenario in the expression of several writers, readers and erasers in PCa [ 145 , 146 , 147 , 148 , 149 ], suggesting the use of combined risk scores of several markers for prognosis prediction [ 145 , 147 , 148 ]. However, other studies have established a clear oncogenic role for increased m 6 A deposition ( Figure 2 B).…”
Section: Epitranscriptomics Alterations In Prostate Cancermentioning
confidence: 99%
“…For example, METTL3 is overexpressed in PCa patients, leading to increased m 6 A RNA methylation [ 146 , 150 , 151 , 152 , 153 ]. In addition, several studies confirmed that METTL3 knocked-down (METTL3-KD) represses the proliferation, tumorigenic invasion, and migration capacity of PCa cells in a catalytic-dependent manner in vitro [ 149 , 150 , 151 , 152 , 153 ], and reduces tumour growth in vivo [ 150 ]. The downregulation of METTL3-mediated m 6 A methylation leads to the alteration of several downstream pathways.…”
Section: Epitranscriptomics Alterations In Prostate Cancermentioning
confidence: 99%
“…They can focus on mRNAs but may include non-coding RNAs, such as miRNAs, lncRNAs or circular RNAs (circRNAs) [ 146 , 147 , 148 , 149 ]. RNA modifications, such as N6-methyladenosine methylation, are also being examined at a large scale due to their impact on stability and splicing [ 150 ]. The potential of gene expression data to provide additive value to traditional clinical parameters for disease progression prediction was shown several years ago in early microarray-based studies [ 151 ] and propelled the hunt for gene transcription signatures of disease recurrence and therapy response.…”
Section: Transcriptomementioning
confidence: 99%